(untitled) (Research, Society and Development, 2024)
Swine farming in Brazil and in the state of Paraná has been a traditional activity implemented in both small and large rural properties. Brazilian swine farming is well established, evident from the country being the fourth-largest producer and exporter of pork globally. The herd is estimated at 2.4 million sows, with a production chain involving around 50 thousand producers. There has been observed growth in the activity, and consequently, there is an increasing interest in the proper disposal of waste and by-products generated by the swineherds across the country. The aim of this study was to characterize the disposal methods for the waste generated by these swine farms. For data collection, on-site visits were conducted, and information on the disposal of carcasses and placental remains was gathered. The survey revealed that 100% of the 67 visited farms use a disposal and treatment system for animal carcasses and placental remains through composting. All farms are in compliance with national and state environmental legislation.